(untitled) (Journal of Nepal Geological Society, 2002)
The inner Lesser Himalayan rocks in the Kusma-Syangja area of Western Nepal comprise the Lower Nawakot Group. Upper Nawakot Group, Sirkot Group, and Tansen Group. The Lower Nawakot Group is made up of the Kuncha Formation (grey-green gritty phyllite and metasandstone), Naudanda Quartzite (very thick, pale yellow to white quartzite), Nayagaun Formation (grey-green phyllite and slate), Nourpul Formation (red-purple, grey, and green-grey phyllitc, slate. and quartzite), and Dhading Dolomite (grey dolomite with columnar stromatolites), respectively from bottom to top. The Dhading Dolomite transitionally passes into the Benighat Slates (interlaminated black slate with sporadic carbonate bands) of the Upper Nawakot Group. The Sirkot Group succeeds the Benighat Slates and is represented by the Sorek Formation (grey-green and red-purple slate and orthoquartzite together with the Ripa Member of grey dolomite containing columnar and dome-shaped stromatolites) and the overlying Dhanpure Limestone (parallel-laminated grey limestone and shale).The Tansen Group disconformably overlies the above reeks, and is represented by the Sisne Formation (grey diamictite), Amile Formation (grey to brown orthoquartzite interbedded with brown and red-purple shale), and Dumri Formation (red-purple shale and grey-green sandstone), respectively in an ascending order. The Lower Nawakot Group is equivalent to the Dantha Group and the Deoban Formation whereas the Benighat Slates arc comparable with the Mandhali Formation in the Kumaon Himalaya, India. Similarly, the Sirkot Group is equivalent to the Kali Gandaki Supergroup and Gwar Group in the outer Lesser Himalaya of Nepal, and the Nagthat, Blaini, and Krol Formations of the Krol Belt in the Kumaon Lesser Himalaya of India. The region underwent intense deformation resulting in the development of foreland- as well as hinterland vergent imbricate faults. The Main Central Thrust (MCT) covered the entire inner Lesser Himalaya in the past and the Kusma-Syangja area was part of a complex duplex system. The MCT was the roof thrust of the duplex and its southward propagation was responsible for the development of south-vergent mesoscopic as well as small-scale folds near the anastomosing leading edge branch lines. A triangle zone was formed in the area bounded by two thrusts with opposite vergence and same basal detachment.